The Effect of Salinity on the Resistance of Plant Cells to Low and Ultra-Low Temperatures on the Example of Dunaliella salina Microalgae Cells - Chernobai, Nadiia; Vozovyk, Krystyna (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):289